Effect of brown midrib gene and maturity at harvest on forage yield and nutritive quality of sudangrass. (12th February 2013) - Beck, Paul; Poe, Kimberly; Stewart, Brandon; Capps, Patrick; Gray, Hannah
Abstract Proper harvest timing of sudangrass [Sorghum bicolor (L.) Moench ssp. drummondii (Nees ex Steud.) de Wet & Harlan] for hay or silage is a compromise between optimized nutrient quality and yield. Brown‐midrib (BMR) sudangrass varieties have reduced lignification and cell wall concentration resulting in increased digestibility. Non‐BMR and BMR sudangrasses were no‐till seeded and harvested at either the boot or dough grain stages of maturity. When harvested at the boot stage of maturity, there was no difference (P = 0.93) in dry matter (DM) yield between the BMR and non‐BMR varieties; while harvesting at the dough grain stage of maturity the BMR variety produced more DM than the non‐BMR variety (P < 0.01). Dry matter and detergent fiber content increased (P < 0.01) and crude protein and calculated total digestible nutrients (TDN) content decreased (P < 0.01) with increasing maturity in both varieties. Regardless of maturity, neutral detergent fiber and acid detergent fiber were less (P < 0.01), and TDN content was greater (P < 0.01) for the BMR sudangrass compared with the non‐BMR variety. Presence of the BMR gene had no effect (P = 0.99) on in situ effective degradability when sudangrass was harvested in the boot stage, but effective degradability was greater (P < 0.01) in BMR sudangrass when harvested in the dough stage of maturity. Inclusion of BMR genetics did not affect performance or digestion kinetics when silage harvested in the boot stage of maturity was fed to growing steers. Brown midrib genetics provide significant advantages when forages are harvested at advanced stages of maturity, but advantages are not as pronounced when forage is less mature.